Nano-priming: Improving plant nutrition to support the establishment of sustainable agriculture under heavy metal stress - Mohammad Faizan; Pooja Sharma; Haider Sultan; Pravej Alam; Shafaque Sehar; Vishnu D. Rajput; Shamsul Hayat (Plant Nano Biology)
Heavy metals (HMs) have become a severe problem for all living organisms, including plants, because of their unprecedented bioaccumulation and biomagnification in the environment. When exposed to hazardous quantities of HMs, various essential cellular macromolecules, including DNA and nuclear proteins, can interact with HMs, causing an overproduction of reactive oxygen species (ROS). Recently, several techniques have been used to ameliorate HM toxicity, including nano-priming, which effectively modulates plant physiological and biochemical responses under HM stress. This review summarizes the literature on the effectiveness of nano-priming for boosting germination, growth, photosynthetic efficiency, biomass accumulation, and crop yield. Additionally, information regarding the application of nano-priming to reduce HM toxicity in plants is reviewed. Future research prospects are indicated by highlighting the knowledge gaps in the current literature and underlining the need optimize and validate nano-priming techniques and their physiological effects on plants.